Deceptive meaning of oxygen uptake measured at the anaerobic threshold in patients with systolic heart failure and atrial fibrillation. (August 2015) - Magrì, Damiano; Agostoni, Piergiuseppe; Corrà, Ugo; Passino, Claudio; Scrutinio, Domenico; Perrone-Filardi, Pasquale; Correale, Michele; Cattadori, Gaia; Metra, Marco; Girola, Davide; Piepoli, Massimo F; Iorio, AnnaMaria; et al.
Background: Oxygen uptake at the anaerobic threshold (VO2 AT), a submaximal exercise-derived variable, independent of patients' motivation, is a marker of outcome in heart failure (HF). However, previous evidence of VO2 AT values paradoxically higher in HF patients with permanent atrial fibrillation (AF) than in those with sinus rhythm (SR) raised uncertainties. Design: We tested the prognostic role of VO2 AT in a large cohort of systolic HF patients, focusing on possible differences between SR and AF. Methods: Altogether 2976 HF patients (2578 with SR and 398 with AF) were prospectively followed. Besides a clinical examination, each patient underwent a maximal cardiopulmonary exercise test (CPET). Results: The follow-up was analysed for up to 1500 days. Cardiovascular death or urgent cardiac transplantation occurred in 303 patients (250 (9.6%) patients with SR and 53 (13.3%) patients with AF, p  = 0.023). In the entire population, multivariate analysis including peak oxygen uptake (VO2 ) showed a prognostic capacity (C-index) similar to that obtained including VO2 AT (0.76 vs 0.72). Also, left ventricular ejection fraction, ventilation vs carbon dioxide production slope, β-blocker and digoxin therapy proved to be significant prognostic indexes. The receiver-operating characteristic (ROC) curves analysis showed that the best predictive VO2 AT cut-off for the SR group was 11.7 ml/kg/min, while it was 12.8 ml/kg/min for the AF group. Conclusions: VO2 AT, a submaximal CPET-derived parameter, is reliable for long-term cardiovascular mortality prognostication in stable systolic HF. However, different VO2 AT cut-off values between SR and AF HF patients should be adopted.